Financial Performance and Stock Price: Evidence from Listed Manufacturing Companies in Sri Lanka - Ekanayake, W.Y.M.M.N.; Indrani, M.W. (University of Jaffna, 2023)
Despite several studies on the effect of financial performance in terms of profitability on stock price, existing literature provides contradictory conclusions regarding this association. Therefore, the main purpose of this study is to explore the effect of financial performance in terms of profitability on stock price, with special reference to the listed manufacturing companies in Sri Lanka from 2011 to 2021. Earnings per Share (EPS), Return on Equity (ROE), and Return on Assets (ROA) were used as proxies of profitability since the current study aims to investigate the aspect of profitability, while the average share price was used as a proxy of stock price. Moreover, the study used three firm-specific control variables, namely, Dividend per Share (DPS), Firm Size (FS), and Debt to Equity (DE). The data was collected from the published annual reports of 29 listed manufacturing companies out of 34 listed manufacturing companies. By employing fixed effect panel regression analysis, this study aims to examine whether there is an effect of financial performance in terms of profitability on stock price. Accordingly, the findings reveal a statistically significant positive effect on stock price in terms of ROA and EPS, despite ROE indicating a negative effect on stock price. Moreover, somewhat simultaneous and divergent results were indicated by the control variables. Accordingly, FS and DE demonstrated a positive association with stock prices. Contrary to this, DPS does not indicate any association with stock price. Moreover, the findings of the study provide insights to investors for encouraging investments and maximizing their investment income, to listed companies for making policy decisions connected with stock price and other investments, and to policymakers for formulating appropriate policies to promote stock investment while regulating credit policies and interest rates.
Keywords: Manufacturing Companies; Stock Price; Financial Performance